Перспективы использования производимых в КНР композитных гранул по технологии LFT-G в производстве перспективного типа конструкционных материалов – нанокомпозитов - Чернобай, Д. В. (БНТУ, 2020)
The possibility of using Chinese raw materials (pellets) made using the LFT-G technology in the production of promising nanocomposite materials (nano-armor and substrates for it) is considered. For comparison and an example, the characteristics of various high-impact materials suitable for creating nanocomposites in the POLYADAMANTIUM project on the territory of the Republic of Belarus are given.